Nilai Estetika dan Pendidikan Naskah Singir Mitera Sejati dan Ngudi Susila Karya Kiai Bisri Musthofa - Shohifur Rizal, Moh. Ahsan (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2016)
â€œSingir mitera sejatiâ€ and â€œngudi susilaâ€ are a literary work that shaped â€œnadhomâ€Â poetically by following the rules of science of arudl. In addition there is an aesthetic andÂ educational value. â€œSingirâ€ can serve as a medium of education and learning resources.Â Because â€œsingirâ€ store â€œadhiluhungâ€ value which can be utilized appropriately, particularlyÂ in the study of literature in the school or boarding school. This research aims to reveal theÂ aesthetic and educational value. Substantially, this research describes about three things,Â namely (1) aesthetic value that includes, (a) the aesthetics of form, and (b) the aestheticÂ contents. (2) the value of moral education that includes (a) the value of moral education whichÂ clarifies the relationship of human with God, (b) the relationship of human with human, (c)Â man human with themself and (d) the human with the environment or nature.